Retrospective Study of Elective Intracranial Tumor Surgery Waiting Time at a National Referral Hospital in Indonesia - Perkasa, Sayyid Abdil Hakam; Rahmah, Habibah Nurul; Arham, Abrar (UI Scholars Hub, 2025)
Elective surgery waiting times are a key measure of healthcare system performance and service quality. Long wait times can lower patients’ quality of life, worsen symptoms, reduce treatment effectiveness, and increase financial stress. We aimed to provide a descriptive analysis of elective surgery waiting time for Intracranial Tumors at Mahar Mardjono National Brain Center Hospital in 2023. This study is a descriptive retrospective cross-sectional study using data from Electronic Health Records (EHR). The study sample included all elective intracranial tumor surgeries performed in 2023. A total of 371 elective intracranial tumor surgeries were analyzed. The median age of patients was 45 years, with the majority being female (64.42%). Most surgeries (44.47%) had a duration of surgery between 3–5 hours with meningioma making up the majority of cases operated (46.63%). The median waiting time for elective intracranial tumor surgery was 44 days, with most patients (72.78%) waiting between 0–3 months. These findings highlight the need for strategies to reduce elective intracranial tumor surgery waiting times. Both short-term and long-term interventions should be implemented, focusing on optimizing resources and expanding surgical capacity. Future studies should examine how these strategies impact patient outcomes and hospital efficiency while identifying potential barriers to their implementation.